CLINICAL AND ANAMNESTIC CHARACTERISTICS OF PREGNANT WOMEN WITH IODINE DEFICIENCY - Александр Николаевич Мацынин; Андрей Викторович Чурилов; Андрей Васильевич Налетов; Игорь Витальевич Коктышев (The Publishing House Medicine and Enlightenment, 2022)
The aim of the research - the purpose of this work was to study of clinical and anamnestic characteristics of pregnant women with insufficient iodine supply, living in the region of natural mild iodine deficiency. Materials and methods. After establishing the thyroid status and the level of consumption of ioduria in 1119 pregnant women, an analysis of the social and clinical and anamnestic data of 465 pregnant women was carried out. Group I consisted of 406 pregnant women with urinary iodine excretion less than 100 µg/l, group II - 59 pregnant women with ioduria over 100 µg/l. Results. The presence of mild iodine deficiency (median ioduria was 76.27 μg/l) was found in the examined pregnant women living in the region of natural iodine deficiency. A high incidence of diseases of the cardiovascular and urinary systems, diseases of the ENT organs, neurocirculatory dystonia was noted in pregnant women of group I, compared with pregnant women of group II. When studying the gynecological and obstetric anamnesis, it was found that uterine leiomyoma and secondary infertility occurred only in pregnant women with iodine deficiency. Premature births in history, despite the absence of statistically significant differences, occurred 1.7 times, pathological births - 5 times more common in pregnant women with iodine deficiency, compared with pregnant women with a normal level of iodine supply, and late births and perinatal losses occurred. only in pregnant women with insufficient iodine intake. Conclusion. It has been established that living in a region of mild natural iodine deficiency in the absence of iodine supplementation is accompanied by the development of iodine deficiency in women during gestation. The lack of adequate iodine supplementation among women living in the region of iodine deficiency is accompanied by the formation of an unfavorable somatic and obstetric-gynecological background, which contributes to a negative impact both on the reproductive potential of a woman and on the course of subsequent pregnancies.